2012
DOI: 10.5966/sctm.2012-0020
|View full text |Cite
|
Sign up to set email alerts
|

Serum- and Stromal Cell-Free Hypoxic Generation of Embryonic Stem Cell-Derived Hematopoietic Cells In Vitro, Capable of Multilineage Repopulation of Immunocompetent Mice

Abstract: Induced pluripotent stem cells (iPSCs) may become a promising source for the generation of patientspecific hematopoietic stem cells (HSCs) in vitro. A crucial prerequisite will be the availability of reliable protocols for the directed and efficient differentiation toward HSCs. So far, the most robust strategy for generating HSCs from pluripotent cells in vitro has been established in the mouse model involving ectopic expression of the human transcription factor HOXB4. However, most differentiation protocols i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Neither the use of AM20.1B4 stromal cells nor the differentiation method based on the transduction of iPSC with the Lhx2 vector , improved the differentiation capacity of these cells (not shown). Moreover, although transplantations of mESC‐derived hematopoietic cells into irradiated recipients resulted in significant hematopoietic engraftments , no reproducible engraftments were observed when A16‐Ex7 c Brca2 Δ 27/ Δ 27 iPSCs were transplanted. In these transplants a reduced number (<1%) of Hox‐B4/EGFP + cells, which did not express hematopoietic markers, could be observed for up to 30 days post‐transplantation in peripheral blood (PB).…”
Section: Resultsmentioning
confidence: 99%
“…Neither the use of AM20.1B4 stromal cells nor the differentiation method based on the transduction of iPSC with the Lhx2 vector , improved the differentiation capacity of these cells (not shown). Moreover, although transplantations of mESC‐derived hematopoietic cells into irradiated recipients resulted in significant hematopoietic engraftments , no reproducible engraftments were observed when A16‐Ex7 c Brca2 Δ 27/ Δ 27 iPSCs were transplanted. In these transplants a reduced number (<1%) of Hox‐B4/EGFP + cells, which did not express hematopoietic markers, could be observed for up to 30 days post‐transplantation in peripheral blood (PB).…”
Section: Resultsmentioning
confidence: 99%
“…), hematopoietic (Lesinski et al. ), and chondrogenic (Koay and Athanasiou ; Adesida et al. ) cells among others.…”
Section: Discussionmentioning
confidence: 99%
“…), and hematopoietic cells (Lesinski et al. ). Recently, differentiation of human ESC into the oligodendrocyte lineage has been accomplished under physiologically relevant 3% oxygen conditions (Stacpoole et al.…”
Section: Introductionmentioning
confidence: 99%
“…These cells further matured towards CD41-CD45+ cells, an important criterion for definitive, adult HSCs. In previous work, we and others have repeatedly shown that such ES cell-derived hematopoietic cells mediate multilineage, longterm repopulation after in vivo transplantation in mice [2,3,[5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…HOXB4 belongs to the family of homeotic selector proteins encoded by homeobox (HOX) genes which are well known for their importance to confer positional information to cells and tissues during embryonic development and to control stem cell self-renewal and differentiation in the adult organism [4]. Human HOXB4, in particular, has repeatedly been demonstrated to enhance the hematopoietic potential of differentiating embryonic stem cells (ESCs) in vitro [1,3,[5][6][7][8][9] and to mediate an expansion of adult HSCs of mice and humans [10][11][12]. However, the underlying mechanisms how HOXB4 mediates these valuable effects are still not understood very well, thus making it a challenging process to decipher the best conditions for translating the results from the mouse to the human system.…”
Section: Introductionmentioning
confidence: 99%